Harnessing magnetic cross-linked cell aggregates (CLCAs) for cost-effective preparation of Konjac mannan-oligosaccharide - Baoyu Cui; Haiqiang Lu; Xue Liu; Yiran Zhang; Xinxi Gu (Microbial Cell Factories)
Abstract Konjac mannan oligosaccharides (KMOS) are currently popular in food additives for their health benefits. However, the simple and efficient preparation of KMOS is still a challenge. In this study, A novel gene encoding β-mannanase (CsMan134) from Cellvibrio sp. KY-GH-1 was displayed on the surface of E. coli cells. Subsequently, E.coli cells (3 g/L) expressing the mannanase CsMan134 were immobilized using 8% (w/v) polyvinyl alcohol, 3% (w/v) sodium alginate, and 3.5% (w/v) Fe₃O₄ to construct magnetic cross-linked cell aggregates (mag-CLCAs). The mannanase CsMan134 demonstrated the highest catalytic efficiency towards konjac mannan compared to other mannans. Compared to free enzyme, the mag-CLCAs exhibited enhanced enzymatic activity across a range of temperatures and pH levels. Furthermore, the mag-CLCAs showed improved thermal stability, retaining over 80% of its initial activity after heating at 50 °C for 180 min, whereas the free enzyme retained only 50% of its residual activity. Scanning electron microscopy (SEM) and vibrating sample magnetometry (VSM) analyses indicated that the mag-CLCAs also maintained good operational stability, retaining more than 75% of their initial activity over five cycles. The mag-CLCAs were effective in converting konjac mannan into a substantial amount of oligosaccharides with a degree of polymerization (DP) of 2–4. In conclusion, the mag-CLCAs represent a valuable, efficient, and cost-effective biocatalyst for the production of KMOS for industrial applications.